Consequences of Social Media in the Everyday Life of People: A Case Study of Kathmandu Valley - K.C., Arjun (Kutumbha vani, 2024)
Social networking has become one of the most important trends of the contemporary society that influenced its members’ communication experiences and perception of reality. This research aims to establish the outcomes of social media use in the lives of the people residing in Ward No. 16 of the Kathmandu Metropolitan City. Social media in particular allows for a broad study of the effects on different parameters the essence of the social interactions among the users of social media, their psychological state, and their ways of obtaining and sharing information. Quantitative and qualitative research methods were used, quantitative and questionnaire based survey and qualitative and interview based survey with 57 respondents. The ideas proposed in this research show that it points to the model of the positive and negative effects, which is the characteristic of social networks as means of communication at the same time. Arguably, the literature suggests that social media results in high consequences in the lives of users with lower age, female gender, lower levels of education, and unmarried statuses. These nuances are discussed in the analysis as a means of providing more information about how people of different age, gender, education level, and marital status perceive the impact of social media. This paper therefore emphasizes the need for people to be conversant with digital literacy, and the need to be cautious when using social media so as to avoid the negative impacts while enjoying the positive ones.